Parameters estimation for the spherical model of the human knee joint using vector method - Ciszkiewicz, Adam; Knapczyk, Józef (Zielona Góra: Uniwersytet Zielonogórski)
Position and displacement analysis of a spherical model of a human knee joint using the vector method was presented. Sensitivity analysis and parameter estimation were performed using the evolutionary algorithm method. Computer simulations for the mechanism with estimated parameters proved the effectiveness of the prepared software. The method itself can be useful when solving problems concerning the displacement and loads analysis in the knee joint.
Keywords: model; knee joint; vector method; estimation; position and displacements